Gestão de Talentos: uma proposta de alto desempenho organizacional e humano - Bispo, Marcelo de Souza (2007)
The thesis will regard the management of human talent into organizations. The main goal of this study was to assess from a managerial point of view, the talents within the organizations and the best way to take lead of it. The research involves an exploratory qualitative study, divided into bibliographic research and field researches, through interviews with company managers and directors with the view of understanding the talent management process in the companies analyzed. The most relevant outcome taken from the research indicated the need to humanize the companies in order to extract the real talent from the people.(AU)